Assessing the tuwid na daan focus on the five key result areas: annexes. - Penalba, Maileenita A. author; Lim, Bryan Albert; Tejero, Lourdes Marie; Ceblano, Christine A.; Alonzo, Rosario I.; Beronilla, Nikkin L.; Mendoza, Ursula; Ofreneo, Rene; Serrano, Isagani R.; Tadem, Climaca; Beltran, Gil S.; Reside, Renato, Jr (Center for Integrative and Development Studies University of the Philippines, 2016)
"The monograph contains thepresentations, supporting graphs or other visual materials that the assessors used during the forums. One may find that by themselves, these documents by individual presenter-assesors could serve as stand-alone analysis on the topics. At best, however, these should be read alongside the analysis of our writers of the "Assessing the Tuwid na Daan: Focus on the Five Key Result Areas" (2015) namely UP Professors Rogelio Alicor Panao and Jan Robert Go.